Malignancies in bullous pemphigoid: A controversial association. Issue 2 (5th October 2015) - Balestri, Riccardo; Magnano, Michela; La Placa, Michelangelo; Patrizi, Annalisa; Angileri, Luisa; Tengattini, Vera; Bardazzi, Federico
Abstract: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disorder that has been reported to be associated with malignancies. Some authors described several cases of pemphigoid associated with malignancies (PAM); however, the evidence of this correlation still remains controversial. Several theories have been postulated to explain the relationship between malignant neoplasms and BP; the main theory suggests that antibodies directed against tumor‐specific antigens of malignant cells may cross‐react with antigens (like BP antigens) in the basement membrane zone leading to the formation of blisters. We performed an extensive review of the English published work focusing on the epidemiology, the pathogenetic theories and the clinical and histological aspects of the disease. We identified 40 cases of PAM: of these, seven cases were associated with hematological malignancies and 33 with solid tumors. Physicians should be aware of the existence of PAM and we suggest an oncological screening in early‐onset pemphigoid, in patients with a former oncological history, in those with signs and symptoms that could be related to a neoplasm and in BP refractory to common immunosuppressive therapy.